Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the problem, we need to identify which given equations represent circles with a diameter of 12 units and a center that lies on the [tex]$y$[/tex]-axis. We will analyze each equation step-by-step.
A general circle equation is given by:
[tex]\[(x - h)^2 + (y - k)^2 = r^2\][/tex]
where [tex]$(h, k)$[/tex] is the center and [tex]$r$[/tex] is the radius. For a circle with a diameter of 12 units, the radius \( r \) is half of the diameter:
[tex]\[r = \frac{12}{2} = 6\][/tex]
So, the radius squared (\( r^2 \)) is:
[tex]\[r^2 = 6^2 = 36\][/tex]
### Analysis of Each Equation
1. Equation: \( x^2 + (y - 3)^2 = 36 \)
- The center is at \((0, 3)\). Since the center lies on the [tex]$y$[/tex]-axis and \( r^2 = 36 \) matches our requirement, this equation is valid.
2. Equation: \( x^2 + (y - 5)^2 = 6 \)
- The center is at \((0, 5)\). While the center lies on the [tex]$y$[/tex]-axis, \( r^2 = 6 \) does not satisfy the radius condition because the radius squared should be 36. This equation is not valid.
3. Equation: \( (x - 1)^2 + 30 = 30 \)
- Rearranging to the general circle form \((x - h)^2 + (y - k)^2 = r^2\), we get \((x - 1)^2 + 0 = 0\). This indicates that it's not a valid circle equation. Thus, it's not valid.
4. Equation: \( (x + 6)^2 + y^2 = 144 \)
- The center is at \((-6, 0)\). The center does not lie on the [tex]$y$[/tex]-axis, so this equation is not valid.
5. Equation: \( x^2 + (y + 8)^2 = 36 \)
- The center is at \((0, -8)\). Since the center lies on the [tex]$y$[/tex]-axis and \( r^2 = 36 \) matches our requirement, this equation is valid.
### Conclusion
The equations that represent circles with a diameter of 12 units and a center that lies on the [tex]$y$[/tex]-axis are:
[tex]\[x^2 + (y - 3)^2 = 36 \][/tex]
and
[tex]\[x^2 + (y + 8)^2 = 36.\][/tex]
Therefore, the correct selections are:
[tex]\[1. \quad x^2 + (y - 3)^2 = 36 \][/tex]
[tex]\[5. \quad x^2 + (y + 8)^2 = 36.\][/tex]
Thus, the two options you should select are:
1. \( x^2 + (y - 3)^2 = 36 \)
2. [tex]\( x^2 + (y + 8)^2 = 36 \)[/tex]
A general circle equation is given by:
[tex]\[(x - h)^2 + (y - k)^2 = r^2\][/tex]
where [tex]$(h, k)$[/tex] is the center and [tex]$r$[/tex] is the radius. For a circle with a diameter of 12 units, the radius \( r \) is half of the diameter:
[tex]\[r = \frac{12}{2} = 6\][/tex]
So, the radius squared (\( r^2 \)) is:
[tex]\[r^2 = 6^2 = 36\][/tex]
### Analysis of Each Equation
1. Equation: \( x^2 + (y - 3)^2 = 36 \)
- The center is at \((0, 3)\). Since the center lies on the [tex]$y$[/tex]-axis and \( r^2 = 36 \) matches our requirement, this equation is valid.
2. Equation: \( x^2 + (y - 5)^2 = 6 \)
- The center is at \((0, 5)\). While the center lies on the [tex]$y$[/tex]-axis, \( r^2 = 6 \) does not satisfy the radius condition because the radius squared should be 36. This equation is not valid.
3. Equation: \( (x - 1)^2 + 30 = 30 \)
- Rearranging to the general circle form \((x - h)^2 + (y - k)^2 = r^2\), we get \((x - 1)^2 + 0 = 0\). This indicates that it's not a valid circle equation. Thus, it's not valid.
4. Equation: \( (x + 6)^2 + y^2 = 144 \)
- The center is at \((-6, 0)\). The center does not lie on the [tex]$y$[/tex]-axis, so this equation is not valid.
5. Equation: \( x^2 + (y + 8)^2 = 36 \)
- The center is at \((0, -8)\). Since the center lies on the [tex]$y$[/tex]-axis and \( r^2 = 36 \) matches our requirement, this equation is valid.
### Conclusion
The equations that represent circles with a diameter of 12 units and a center that lies on the [tex]$y$[/tex]-axis are:
[tex]\[x^2 + (y - 3)^2 = 36 \][/tex]
and
[tex]\[x^2 + (y + 8)^2 = 36.\][/tex]
Therefore, the correct selections are:
[tex]\[1. \quad x^2 + (y - 3)^2 = 36 \][/tex]
[tex]\[5. \quad x^2 + (y + 8)^2 = 36.\][/tex]
Thus, the two options you should select are:
1. \( x^2 + (y - 3)^2 = 36 \)
2. [tex]\( x^2 + (y + 8)^2 = 36 \)[/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.